Lipid Pattern and atherogenic index among medicalstudents - Ahmed, Afsana; Ara, Shamim; Nahar, Lutfun; Kabir, Md Shahjahan; Sharmin, Shafia (Journal of Dhaka National Medical College & Hospital, 2014)
Background & Objective: In Bangladesh young age group has received little attention in relation to lipid profile & atherogenic index. For this purpose we decided to see lipid pattern & atherogenic index of plasma (AIP) among medical students. Method: In a cross sectional approach, 90 apparently healthy medical students voluntarily recruited from Ist year of Dhaka National Medical college during the period of June,2013 to December,2013. Height, weight, BMI, blood pressure were measured. Total cholesterol (TC), and the various sub fractions; high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and triglycerides (TG) were determined. Atherogenic index of plasma (AIP); log (TG/HDL-C) was calculated, in accordance with the most recent guidelines issued by the American Heart Association (AHA)/American College of Cardiology (ACC) and the National Cholesterol Education Program (NCEP). Results: Among the total students 56.66% had normal BMI, 13.33% were found to be underweight. 23.33% & 6.66% were overweight & obese respectively. Out of 90 students, 22 had low HDL (<40 mg/dl), 11 had increased TG (>150 mg/dl), 5 had increased Cholesterol (>200 mg/dl), 3 had increased LDL (>130mg/dl). Among the students 41 had low cardiovascular risk which represents 45.5%, 45 had increased cardiovascular risk which represents 50%, & 4 had intermediate cardiovascular risk which represents 4.44%. Conclusion: By assessing AIP we found that 41 subjects had low cardiovascular risk which represents 45.5%, 45 had increased cardiovascular risk which represents 50%, & 4 had intermediate cardiovascular risk which represents 4.44%, A high prevalence of cardiovascular risk factors; family history of elevated blood pressure was present. J. Dhaka National Med. Coll. Hos. 2014;20(01):37-40